ANALISIS KELAYAKAN KUALITAS BATAKO HASIL PRODUKSI INDUSTRI KECIL DI KOTA PAYAKUMBUH DAN KABUPATEN LIMA PULUH KOTA - Elvi Syamsuir (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Research on the Feasibility Analysis Quality brick Production of Small Industries inPayakumbuh and Kabupaten Lima Puluh Kota has been conducted to determine thefeasibility of quality adobe result of small industries in Payakumbuh and Kabupaten LimaPuluh Kota and to know how to optimize the mix of brick that worthy quality standardsappropriate with the requirements PUBI-1982. Tests done after the adobe brick was only28 days. Equipment for the testing of compressive strength of concrete blocks arecompression machine. Test Results Compressive Strength average compressive strengthvalues obtained brick on brick in Civil Engineering Laboratory STT Payakumbuh hasincreased and decreased. The compressive strength was lowest for the BA sample (amixture of 1: 6) with an average compressive strength of 0.7 MPa while the compressivestrength is highest in BC samples (a mixture of 1: 5) with an average compressive strengthof 3.1 MPa. Of 5 small brick industry in Payakumbuh and Kabupaten Lima Puluh Kota, 3of which can not be said to be feasible because it does not meet the standards PUBI-1982.Small industries which include this category are from Tanjung Pati (BA), Tiakar (BD) andthe Village of Sand.Keywords: Batako, Quality of Batako, Compressive strength Tested